PROBABLE CHARACTERISTICS ОF ELECTROMAGNETIC FIELD ENVIRONMENT AT EARTH SURFACE CAUSED BY RADIO-ELECTRONIC AIDS OPERATING OVER EARTH SURFACE - V. I. Mordachev (Наука и техника)
The paper provides results of modeling distribution of signal probability of radio-electronic aids located over the Earth surface at a specific height and determining an electromagnetic environment on its surface according to a power parameter and an input direction angle at an optionally selected observation point being on the earth surface.